Implementasi Pembelajaran Kolase sebagai Upaya Edukasi Fauna di Sekolah Dasar - Cahaya Safitri Ningsih; Moh Rusnoto (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This research aims to determine students' understanding of Indonesian fauna through collage learning. This research uses a qualitative research approach. The sample in this research is class 2 students at SD Negeri Puro Pakualaman 1 consisting of 7 children. The data collection techniques used are observation and tests. Data analysis in this study used a comparison of the average pretest and posttest results. The research results showed that the average score had increased by 22%. Thus, collage learning was able to increase students' understanding of Indonesian fauna. The collage learning carried out is able to foster children's enthusiasm for participating in the learning being carried out.